LIVELIHOOD CHALLENGES AND COPING STRATEGIES OF AGRICULTURAL WORKERS DURING COVID-19 PANDEMIC - Tanjina Afrin; Fariha Nowshin; Md. Ismail Hossain (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Bangladesh is one of the high-risk countries of the COVID-19 pandemic and its consequent losses. The main objectives of this research were to find out the livelihood challenges and coping strategies of agricultural workers during pandemic situation. This study was conducted targeting lower income group of people (temporary agricultural worker, casual agricultural workers). As the nature of the research was qualitative, the researcher used convenience sampling to select respondents because this is the most common non-probability sampling strategy where respondents were selected in an ad hoc fashion based on their accessibility. However, the researcher has taken 60 respondents as sample in analyzing data, descriptive statistics (frequency and percentage) of responses are estimated. Scores of livelihood challenges are the means of a 4-point Likert-type scale used. From this study find that most of the respondents did small business but they did not get any help or small loan from NGO. Most of the respondents drive rickshaw, auto as their off day. Due to closing of school, respondents’ children engage themselves to earning activities. Key words: Covid-19 pandemic, coping strategies, Livelihood challenges , Agricultural workers